Prevalence of alcohol abuse among workers in Italy - Venturelli, Francesco; Poscia, Andrea; Carrozzi, Giuliano; Sampaolo, Letizia; Bargellini, Annalisa; Ricciardi, Walter; Magnavita, Nicola (La Medicina del Lavoro, 2017)
Background: Unhealthy alcohol consumption among workers increases the risk of job-related injuries and reduces productivity. Therefore, preventing workplace alcohol abuse is a public health priority. Objectives: This study is based upon data collected by PASSI and aims to outline the prevalence and socio-demographic characteristics of alcohol consumption among workers in Italy. Methods: PASSI is a nationwide surveillance system that examines health-related behaviours and the degree of knowledge and adherence to the preventive interventions offered by the Italian National Health Service. Between 2010 and 2013, 101,002 telephone interviews were collected from a sample of residents aged 18-69, randomly selected from local health unit lists. Results: 45.3% of those interviewed declared to be abstemious, while 16.5% reported an unhealthy alcohol drinking, with a higher prevalence among workers than non-workers (18.0% vs 14.2%, p